1999
DOI: 10.1183/09031936.99.14511909
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a simple scoring system applied to a screening questionnaire of asthma in children aged 5-15 yrs

Abstract: The aim of the present study was to validate a simple scoring system using a parent-completed screening questionnaire to identify children aged 5±15 yrs who may have asthma.A stratified random sample of 157 children of 1,808 whose parents had answered a postal respiratory questionnaire underwent detailed clinical evaluation. The results were reviewed by three independent paediatricians whose opinions were combined to reach, for each child, decisions regarding three standards: 1) "possible asthma" defined as >5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 19 publications
0
48
0
Order By: Relevance
“…1 Increase in the rates of hospital admission and primary care contacts for asthma in childhood has led to concern regarding prevalence or severity of increasing wheezing illness in children. Rise in prevalence of childhood asthma is a matter of concern worldwide and in India also.…”
Section: Introductionmentioning
confidence: 99%
“…1 Increase in the rates of hospital admission and primary care contacts for asthma in childhood has led to concern regarding prevalence or severity of increasing wheezing illness in children. Rise in prevalence of childhood asthma is a matter of concern worldwide and in India also.…”
Section: Introductionmentioning
confidence: 99%
“…Children who were likely asthmatics, if not known to the practice, would require clinical assessment to determine their asthma status. An evaluation of this scoring system [11] has shown that increasing numbers of positive responses to these key questions increase the likelihood of a child benefiting from a trial of asthma medication. Three or more positive responses had a positive predictive value (PPV) of 84% (95% confidence interval (CI) 74 -90) to identify such children who were, therefore, classed as "likely asthmatics".…”
Section: Methodsmentioning
confidence: 99%
“…The WYCAP questionnaire has been validated for use in children aged between 5 and 15 years. 8 Skin prick tests were carried out to identify the prevalence of atopic sensitisation.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire (see Appendix A, available online at www.thepcrj.org), a modified version of the ISAAC core questionnaire for wheezing and asthma, 6 was based on that used in the Wythenshawe Community Asthma Project (WYCAP). 8 Reminders were sent to non-responders after four and eight weeks and at the end of the distribution period. The return of a completed questionnaire was considered as consent to participate in the study.…”
Section: Methodsmentioning
confidence: 99%